MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PEMBELAJARAN KOOPERATIF LEARNING TOGETHER - M. Thoha, - (Universitas Islam Darul Ulum, 2016)
The purposes of the study were (1) improving the way of learningÂ Islamic Education by implementing cooperative learning together and (2) enhancing the students motivation then can increase the quality of studentsâ learning. The study was conducted in the fourth grade at the first state elementary school of Kembangbahu by the number of students were 10 in the second semester of the 2015/2016 academic year. It took two cycles by implementing the cooperative learning together in learning Islamic education. The conclusion of this research was the implementation of cooperative learning together and cooperative learning together model effect on studentsâ motivation and their learning achievementÂ thus indirectly the quality of learning Islamic education at the first state elementary school of Kembangbahu, District Kembangbahu, Lamongan increased. Shown in the first cycle of the average value of 61.5 and increased in the second cycle became 83. Thus it can be said that the learning achievement of Islamic education through cooperative learning together in the fourth graders of the first state elementary school of Kembangbahu, District Kembangbahu, Lamongan in the academic year of 2015/2016 increased.